2008
DOI: 10.1073/pnas.0805108105
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication of lakes cannot be controlled by reducing nitrogen input: Results of a 37-year whole-ecosystem experiment

Abstract: Lake 227, a small lake in the Precambrian Shield at the Experimental Lakes Area (ELA), has been fertilized for 37 years with constant annual inputs of phosphorus and decreasing inputs of nitrogen to test the theory that controlling nitrogen inputs can control eutrophication. For the final 16 years (1990 -2005), the lake was fertilized with phosphorus alone. Reducing nitrogen inputs increasingly favored nitrogen-fixing cyanobacteria as a response by the phytoplankton community to extreme seasonal nitrogen limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
858
12
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,465 publications
(918 citation statements)
references
References 32 publications
31
858
12
17
Order By: Relevance
“…Bottle bioassays or mesocosm studies are often conducted on a relatively small scale and cannot properly account for important long-term processes such as atmospheric exchange, changes in the grazer community, and nutrient exchange with sediments (Schindler et al 2008). Therefore, generalizations from bioassay experiments to the real situation in the field must be drawn with caution (Hecky and Kilham 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottle bioassays or mesocosm studies are often conducted on a relatively small scale and cannot properly account for important long-term processes such as atmospheric exchange, changes in the grazer community, and nutrient exchange with sediments (Schindler et al 2008). Therefore, generalizations from bioassay experiments to the real situation in the field must be drawn with caution (Hecky and Kilham 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some research argue that P is the ultimate limiting nutrient overtime since N 2 fixation helps satisfy N requirements (Schindler et al 2008). In fact, N limitation has been observed in whole-lake experiments and many studies have indicated that N 2 fixation by phytoplankton cannot fully compensate for nitrogen deficiency (Kolzau et al 2014;Lewis and Wurtsbaugh 2008;Paerl 2009;Scott and McCarthy 2010).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Input of excessive phosphorus (P) from non-point source wastewater is an important cause for eutrophication of surface water bodies, such as lakes, rivers, reservoirs etc., and thus pose many environmental, economic and social problems (Chen et al, 2015;Schindler et al, 2008;Smith & Schindler, 2009). As a result, many technologies are currently in place to remove excess P from wastewaters, among them biological methods using phototrophic periphyton is a subject of great concern (Boelee et al, 2011;Guzzon et al, 2008;Roeselers et al, 2008;Shi et al, 2007;Sukačová et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their differences, all three lakes have suffered from serious N pollution (Liu et al 2009;Frumin and Khuan 2012). The relationship between nutrient concentrations and eutrophication of lakes has been a debate for decades, focusing on whether N or P is the limiting factor for eutrophication (Paerl et al 2004;Bergström and Jansson 2006;Schindler et al 2008;Conley et al 2009;Scott and McCarthy 2010). Generally, nutrient limitation for eutrophication of lakes is a case-specific question, depending on various factors such as temperature (Moss et al 2013), N deposition (Elser et al 2009), lake age (Moss et al 2013), and nutrient loading (Paerl et al 2011).…”
Section: Introductionmentioning
confidence: 99%